Augmented Reality sebagai alat Pembelajaran Inovatif: Implikasinya terhadap Pengembangan Grit dalam Pendidikan - Rifqi Aminul; Elok Halimatus Sa'diyah; Rifa Hidayah (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2024)
Innovative learning with Augmented Reality technology today is a trend in modern schools, in Indonesia and abroad. As technology develops massively in education, it will affect students' cognitive, emotional, and psychomotor development. Then this article will examine, as technology develops in education, how this affects the development of grit in students. Saving researchers have two important questions, first, how Augmented Reality technology as learning in the world of education. Second, how the development of grit in the education world. The method used is qualitative with the library research approach of primary data sources from books on augmented reality and grit as well as secondary data from internationally renowned scientific articles, methods of analysis are descriptive analytical, by implicitly describing and analysing how innovative learning as grit development in students. The results of this study prove first Augmented Reality has been shown to enhance student interest, understanding, and involvement in the material of the lesson, so that the grit in the student can unconsciously grow. Second, the concept of grit development includes perseverance, and the spirit in facing the challenge, can be enhanced through learning experiences that require exploration and problem solving, in the use of Augmenting Reality students are able to think creatively and critically in receiving the material.